AN ANALYSIS OF POLITENESS PRINCIPLES IN THE SMALLFOOT MOVIE - Elin Ayu Istiyana Uly; Arin Inayah; Tri Mulyati (LUNAR, 2022)
This research is a descriptive study on the use of politeness principle in the Smallfoot movie. The researcher employed descriptive qualitative method by collecting the utterances of the movie. This research aimed to identify the types of politeness principles used by the main character in the Smallfoot movie . This research analyze the politeness principles by using Brown and Levinson (1978) politeness theory. The result show that Smallfoot movie consists four types of politeness principles. They are 7 bald-on record, 8 positive politeness, 4 negative politeness and 2 off-record. In the types of politeness principles used by the main character consist 70 utterances they are 34 (48,5%) utterances of bald-on record, 25 (35,7%) utterances of positive politeness, 8 (11,5%) utterances of negative politeness and 3 (4,3%) utterances of off-record. Based on the result of this study, the researcher expects this study gives contributions to the researcher herself and the readers and for further researcher who interseted in analyzing movie